The Effectiveness of Relaxation Massage on Sleep Quality in Pregnant Women at PMB Deliana, Marpoyan Damai District, Pekanbaru City - Riza Febrianti; Ani Triana (Journal of Midwifery and Nursing, 2021)
Hormonal changes, weight gain and changes in body posture are some of the factors that cause back pain that often occurs during pregnancy (Mufdlilah, 2009). In the process of pregnancy, complaints always arise, one of which is very disturbing is the problem of back pain during pregnancy. Back pain during pregnancy is usually experienced by women at certain times during pregnancy, usually in the third trimester of pregnancy. Back pain is common in pregnancy with the reported incidence varying from approximately 50% in the UK and Scandinavia to close to 70% in Australia. The research objective of this study was to determine how relaxation massage affects sleep quality in pregnant women. The research method isThe type of research conducted is quasi-experimental (quasi-experimental) which is a research plan that is structured in such a way that it can lead researchers to obtain answers to researchers (Notoatmodjo 2010). The results of the study obtained a p value = 0.000 so that H0 was rejected, it was concluded that there was an effect of relaxation massage on the quality of sleep for pregnant women (p <0.000), so it could be concluded that there was an effect of relaxation massage given to pregnant women on the quality of sleep of mothers. It is hoped that further research will be able to examine different variables so that they can find out how to improve sleep quality for pregnant women